2019
DOI: 10.21203/rs.2.11334/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mild water stress-induced priming enhance tolerance to Rosellinia necatrix in susceptible avocado rootstocks

Abstract: Background: White root rot (WRR) disease caused by Rosellinia necatrix is one of the most important threats affecting avocado orchards in temperate regions. The eradication of WRR is a difficult task and environmentally friendly control methods are needed to lessen its impact. Priming plants with a stressor (biotic or abiotic) can be a strategy to enhance plant defense/tolerance against future stress episodes but, despite the known underlying common mechanisms, few studies use abiotic-priming for improving tol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Moreover, qRT-PCR quantification of the defence protease inhibitor gene, showed a 4-and 5-fold increases following elicitation with salicylate and jasmonate, respectively, in root samples after 12 hours (Clara Pliego, IFAPA-Málaga, unpublished results, May, 18, 2020). Previous investigations, also in avocado plants, had shown that exposure to mild water stress improved plant response to White Root Rot (cross-factor priming) [29]; the improved performance of avocado plants was linked to a general increased expression of plant defence genes, in particular those coding for NPR1 protein and NAC domain containing protein 72, leading these authors to conclude that adequate irrigation management could be an useful strategy to control fungal infections in commercial avocado orchards. In rice, Samota [30] observed that seed elicitation with methyl jasmone induced changes in expression of drought responsive genes RD1 and RD2 and plants derived from the elicited seeds would respond better to water stress than those from control seeds.…”
Section: Primingmentioning
confidence: 99%
“…Moreover, qRT-PCR quantification of the defence protease inhibitor gene, showed a 4-and 5-fold increases following elicitation with salicylate and jasmonate, respectively, in root samples after 12 hours (Clara Pliego, IFAPA-Málaga, unpublished results, May, 18, 2020). Previous investigations, also in avocado plants, had shown that exposure to mild water stress improved plant response to White Root Rot (cross-factor priming) [29]; the improved performance of avocado plants was linked to a general increased expression of plant defence genes, in particular those coding for NPR1 protein and NAC domain containing protein 72, leading these authors to conclude that adequate irrigation management could be an useful strategy to control fungal infections in commercial avocado orchards. In rice, Samota [30] observed that seed elicitation with methyl jasmone induced changes in expression of drought responsive genes RD1 and RD2 and plants derived from the elicited seeds would respond better to water stress than those from control seeds.…”
Section: Primingmentioning
confidence: 99%